Família e cooperativismo: o ethos cooperativista na região de Franca/SP - Barbosa, Cristiane Olegário [UNESP] (2015)
This work presents the research developed that sought to know the impact of cooperativism in the daily cooperative families of a cooperative in the region of Franca, with the aim to identify the power of cooperativism as a form of economic and social development and knowing whether its members have awareness and understanding about its proposal. The first part of the text approaches the history of Cooperatives in the region of Franca / SP through the history of Coffee Growers and Agriculturists' Cooperative, the universe of this research and its product, the coffee, that it's the fruit of the work of more than two thousand members of this institution. This research discusses about the families and work in capitalist sociability, presenting the family nucleus as the fundamental element of society and important participant of production relations in everyday social life. The cooperativist historicity was described since the beginning in Rochdale, in England, until its structure in the current modern, as the cooperative enterprises, its branches of actuation and its representation in the world. In addition, presenting a special way, the cooperativist principles published by the economic and social development mode. The second part of this work discourses about the cooperativist culture and the way of experiencing the principles and collective economic practice. The dissertation also proposes a reading evincing the cooperativism's contributions to the development of values such as citizenship, cooperation and education for families and society. Finally, points out the dimensions of the professional work of Social Worker, the materialization of the theoretical framework in the professional exercise and the arduous task of building professional identity seeking to overcome the adversities in working with families and in the cooperative. The themes covered in the text are fundamental elements of working world...